1993
DOI: 10.1007/bf02822189
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors associated with low birth weight

Abstract: Maternal factors comprising of social, obstetric and anthropometric are found to influence LBW. The present study had found association between obstetric risk factors like age of the mother, parity and gravida with LBW. Similar association was also observed between maternal height, and maternal weight with LBW. However, social factors were not found to be associated with LBW. This could probably be due to RUHSA's intervention which requires a further inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 9 publications
6
21
1
Order By: Relevance
“…13 Amin et al found that around 50% of mothers in each educational level were found to deliver LBW babies, indicating no effect of mother's education on LBW. 14 In the present study, percentage of low birth weight was higher in mothers having height less than 140 cm (28%) and in 140-145 cms (28.5%). A highly significant association was found between maternal height and birth weight of baby (p<0.001).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…13 Amin et al found that around 50% of mothers in each educational level were found to deliver LBW babies, indicating no effect of mother's education on LBW. 14 In the present study, percentage of low birth weight was higher in mothers having height less than 140 cm (28%) and in 140-145 cms (28.5%). A highly significant association was found between maternal height and birth weight of baby (p<0.001).…”
Section: Discussionsupporting
confidence: 43%
“…15 Amin et al found 61.7% mothers with height <150cm delivered LBW babies, which was statistically not significant. 14 In the present study, the percentage of low birth weight babies was higher in second para and above (18%) compared with primiparous mothers (14%). Joshi and Pai observed that the percentage of LBW increased with increase in parity.…”
Section: Discussionsupporting
confidence: 40%
“…This is in accordance with the studies of Roth et al 5 A significant association between primiparity and VLBW was observed in this study. This was comparable with the previous studies of Amin et al, Mallik et al 6,7 The incidence of VLBW is high when birth interval is less than 2 years than compared to birth interval more than 2 years. This may be due to a minimum period of 2-3 years for the mother's nutrition and general condition to attain the pre-pregnancy level.…”
Section: Discussionsupporting
confidence: 92%
“…The difference revealed was statistically significant. This finding was similar to previous studies which revealed that primiparity is significantly associated with LBW [27,28]. It is considered that BMI is a good marker for the tissue nutrient reserves [29].…”
Section: Discussionsupporting
confidence: 92%